EFFICACY OF DENTAL IMPLANTATION IN THE COMPREHENSIVE REHABILITATION OF PATIENTS FOLLOWING COMBINED TREATMENT FOR MAXILLOFACIAL NEOPLASMS (Ustozlar uchun, 2026)
A comprehensive examination and treatment of 30 patients, divided into two groups, was conducted. The main group (15 patients) had previously undergone chemoradiotherapy (total focal dose of 30–65 Gy), while the control group (15 patients) comprised somatically healthy individuals. Implantation was performed according to a two-stage protocol (remission period > 6 months). CBCT, orthopantomography (OPTG), and histomorphometric analysis of trephine biopsy specimens were utilized to evaluate bone tissue status and osseointegration.